Penerapan Sistem Agroforestri pada Perkebunan Kopi di Blang Gele, Kecamatan Bebesen, Kabupaten Aceh Tengah - Aini Syafitri; Anggi Pratiwi; Citra Dara Mutia; Dhea Rhamadini; Dila Maiyana; Fayza Meutia; Khairunisak Khairunisak; Maulida Ayu Mardana; Nadya Tirta; Nazila Munawira; Rasyadhifa As Sahira; Salsabilla Salsabilla; Syafira Azzahra; Syifa Thifal Umaira; Januardi Januardi; Wira Dharma; Zuriana Siregar; Saida Rasnovi; Dahlan Dahlan (Universitas Syiah Kuala, 2024)
This research aims to identify the types and agroforestry systems of coffee plantations in Blang Gele, Central Aceh. The methods used are surveys and interviews. The results of this research show that there are 3 types of coffee varieties planted, namely Gayo 1, 2, and 3 varieties, interspersed with shade plants in the form of lamtoro, banana, cabbage, shallots, and andaliman with simple and complex agroforestry systems. The implementation of a coffee agroforestry system with economically valuable shade crops provides more diverse and higher income for farmers, which encourages farmers to optimize land use with a mixed cropping system, thereby increasing the sustainability of coffee farmers' income in the area. The conclusions of this research emphasize the importance of agroforestry systems in increasing the income of coffee farmers in Central Aceh through crop diversification. Thus, implementing agroforestry can be a sustainable strategy in cultivating coffee in this area.